Streptozotocin-induced diabetes mellitus affects lysosomal enzymes in rat liver - Peres,G.B. (2014)
It has been previously shown that dextran sulfate administered to diabetic rats accumulates in the liver and kidney, and this could be due to a malfunction of the lysosomal digestive pathway. The aim of the present study was to evaluate the expression and activities of lysosomal enzymes that act upon proteins and sulfated polysaccharides in the livers of diabetic rats. Diabetes mellitus was induced by streptozotocin in 26 male Wistar rats (12 weeks old), while 26 age-matched controls received only vehicle. The livers were removed on either the 10th or the 30th day of the disease, weighed, and used to evaluate the activity, expression, and localization of lysosomal enzymes. A 50-60% decrease in the specific activities of cysteine proteases, especially cathepsin B, was observed in streptozotocin-induced diabetes mellitus. Expression (mRNA) of cathepsins B and L was also decreased on the 10th, but not on the 30th day. Sulfatase decreased 30% on the 30th day, while glycosidases did not vary (or presented a transitory and slight decrease). There were no apparent changes in liver morphology, and immunohistochemistry revealed the presence of cathepsin B in hepatocyte granules. The decrease in sulfatase could be responsible for the dextran sulfate build-up in the diabetic liver, since the action of sulfatase precedes glycosidases in the digestive pathway of sulfated polysaccharides. Our findings suggest that the decreased activities of cathepsins resulted from decreased expression of their genes, and not from general lysosomal failure, because the levels of glycosidases were normal in the diabetic liver.